VD_FINDINFO Jug / 2012 / 247 vom 19. September 2012 - VD Tribunal cantonal (2012)
DÉCISION D'IRRECEVABILITÉ, ASSURANCE COMPLÉMENTAIRE, COMPÉTENCE RATIONE MATERIAE | 12 al. 2 LAMal, 12 al. 3 LAMal, 94 al. 1 let. a LPA-VD, 404 CPC (CH)